5/6(x)-3x+8/3=5/3

Simple and best practice solution for 5/6(x)-3x+8/3=5/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/6(x)-3x+8/3=5/3 equation:


x in (-oo:+oo)

(5/6)*x-(3*x)+8/3 = 5/3 // - 5/3

(5/6)*x-(3*x)+8/3-(5/3) = 0

(5/6)*x-3*x+8/3-5/3 = 0

1-13/6*x = 0 // - 1

-13/6*x = -1 // : -13/6

x = -1/(-13/6)

x = 6/13

x = 6/13

See similar equations:

| y=cos^3(2x^4) | | x+0.05x=467.84 | | 9(v+2)-3v=2(3v+3)-11 | | y=4x^4tan(5x) | | -23p-5(4-6p)=3(p-3)-35 | | y=-2/3x+2 | | 4+4x=620 | | 13+1x=44 | | 14-18x=104-29x | | x^2+kx-8=0 | | 4-6*2/2+2 | | 3p^2-18p=0 | | 7x-3=-5+6x(4x+3) | | 2x+2(.375)=3.00 | | 8x+3y=6.50 | | 2/4+1/3 | | =(x-4+i)(x-4-i) | | x+4-6+15x-3x=19x-8+20-7 | | 2x*5=9x-(5/4) | | 12.21-4.3a=24.25 | | =[x-(4-i)][x-(4+i)][x-(4-3i)][x-(4+3i)] | | 3(7r-7)=-6r+6r | | 2x+65=75 | | 3(7r-7)=-6r-6 | | 14k-10=12k | | C(q)=3q^2+20q+10 | | 4y+2x=48 | | 2(x+6)=3(x+5) | | 7q+4q=88 | | 230-7x=38x+20 | | x^2-0.5x-3=0 | | -6-21=r |

Equations solver categories